Natural occurrence of entomophthoroid fungi (Entomophthoromycota) of aphids (Hemiptera: Aphididae) on cereal crops in Argentina - Manfrino, Romina Guadalupe; Hatting, J.L.; Humber, Richard; Salto, Cesar Eduardo; Lopez Lastra, Claudia Cristina (2018)
The spectrum of entomophthoroid fungal species parasitising aphids on cereal crops and a study of the phenology and prevalence of these pathogens were investigated in Argentina. The studies were conducted at six different sites cultivated with crops of Triticum aestivum (wheat), Avena sativa (oats) and Sorghum bicolor (sorghum) during two consecutive years. Entomopathogenic fungi from the new phylum Entomophthoromycota were recorded from six aphid species on cereals in Argentina: Rhopalosiphum maidis, Rhopalosiphum padi, Rhopalosiphum rufiabdominalis, Schizaphis graminum, Sitobion avenae and Sipha maydis. Three species of entomophthoroid fungi were found infecting these aphid species: Pandora neoaphidis, Zoophthora radicans (Entomophthorales: Entomophthoraceae) and Neozygites fresenii (Neozygitales: Neozygitaceae). Entomophthoroid fungal infections occurred mostly in autumn–winter seasons (March–August), and coincided with periods of high relative humidity and comparatively low temperatures. This study represents the first base‐line characterisation of entomophthoroid fungi infecting aphids on cereal crops in Argentina.